Pengaruh Pembelajaran Kooperatif Tipe STAD dengan Bantuan Website terhadap Kemampuan Pemahaman Konsep Geometri Siswa Kelas VIII - Umam, Khoerul; supiat, Supiat (Universitas Hamzanwadi, 2019)
This study aims to determine the differences in STAD type cooperative learning on geometry material integrated with the website www.fooplot.com. The subject of this study was a private junior high school in Bekasi, which is consisted of 31 male students and 40 female students. This study uses a quasi-experimental design method. Data from the research will be analyzed using descriptive statistics. The results of the study have shown that learning mathematics using a website has assisted students to improve their understanding of geometric concepts. The learning with the website has supported students to study independently outside of school hours. Website applications can encourage students to examine student work independently.